HOMOMORFISMA DARI LEVEL SUBNEAR-RING FUZZY - Saman Abdurrahman (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2014)
This paper introduces the concept of subnear-ring level in the fuzzy subnear-ring. Result of this study is the image and pre-image homomorphism of the near-ring of the inner subnear-ring level The fuzzy subnear-ring is the subnear-ring level in the fuzzy subnear-ring.